Blue phases as templates for 3D colloidal photonic crystals - Zumer, S; Ravnik, M; Porenta, T; Alexander, G; Yeomans, J (2010)
We examine the possibilities to use the intrinsic 3D defect networks in blue phases I and II as arrays of trapping sites for colloidal particles. Our approach based on the phenomenological Landau-de Gennes description and topological theory has proven to be extremely useful in dealing with nematic colloids. A perturbed orientational order leads to effective anisotropic long range inter-particle coupling and consequently to numerous organizations of colloidal particles not present in simple liquids. Recent developments that led to the blue phases with extended stability range make them more attractive for use. In these phases the competition between nematic ordering and intrinsic tendency to form double twisted deformations yields complex director patterns and disclination networks. The spatially deformed order that mediates the attraction of particles to the network sets the ground for a possible self-assembling of 3D superstructures with extended stability ranges. Here we first describe the trapping mechanism on the case of a single discilination line and then use the results to demonstrate the trapping in the blue phase II. Effects of particle sizes ranging from submicron to 50 nanometers are examined. The assembling in blue phases is expected to form photonic crystals that can be easily manipulated via affecting the liquid crystal matrix and/or colloidal particles. © 2010 SPIE.